Spatial data needs to support local decision making in rural landscapes :Powerpoint - Willemen, L. (University of Twente, 2020)
This lecture presents: ES in rural landscapes; Agriculture‐dominated landscapes; Landscape approaches; Why landscape interventions?; Supporting landscape interventions; SpatialGuide Development; Spatial data & Local action in Ethiopia.